2000
DOI: 10.1002/1096-8628(20001211)95:4<339::aid-ajmg9>3.3.co;2-2
|View full text |Cite
|
Sign up to set email alerts
|

Head circumference is an independent clinical finding associated with autism

Abstract: Occipitofrontal circumference (OFC) is one of the few physical findings in autism that varies significantly from the norm and is distinct and measurable. As part of a study of genetic heterogeneity of autism, we scrutinized data from a large sample of patients with idiopathic autism (N = 137), using OFC as the categorizing variable. The OFC standard deviation (OFCSD) values of the autistic propositi (0.61+/-1.6) varied significantly from that of the normal population (0.0+/-1.0), (P<0.001). Comparison of the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
57
0
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(65 citation statements)
references
References 46 publications
(57 reference statements)
7
57
0
1
Order By: Relevance
“…Kanner, the first to report on autism, noticed the presence of enlarged heads in some children with autism (Kanner, 1943). Several subsequent studies have replicated this finding both in children and in adults (Aylward, Minshew, Field, Sparks, & Singh, 2002;Bailey, Luthert, & Bolton, 1993;Davidovitch, Patterson, & Gartside, 1996;Fidler, Bailey, & Smalley, 2000;Fombonne, 2000;Gillberg & de Souza, 2002;Lainhart et al, 1997;Miles, Hadden, Takahashi, & Hillman, 2000;Stevenson, Schroer, Skinner, Fender, & Simenseh, 1997;Woodhouse, Bailey, Rutter, Bolton, & Baird, 1996). Likewise, neuropathological studies have reported increased brain weight in a subset of subjects with autism.…”
Section: Introductionmentioning
confidence: 86%
“…Kanner, the first to report on autism, noticed the presence of enlarged heads in some children with autism (Kanner, 1943). Several subsequent studies have replicated this finding both in children and in adults (Aylward, Minshew, Field, Sparks, & Singh, 2002;Bailey, Luthert, & Bolton, 1993;Davidovitch, Patterson, & Gartside, 1996;Fidler, Bailey, & Smalley, 2000;Fombonne, 2000;Gillberg & de Souza, 2002;Lainhart et al, 1997;Miles, Hadden, Takahashi, & Hillman, 2000;Stevenson, Schroer, Skinner, Fender, & Simenseh, 1997;Woodhouse, Bailey, Rutter, Bolton, & Baird, 1996). Likewise, neuropathological studies have reported increased brain weight in a subset of subjects with autism.…”
Section: Introductionmentioning
confidence: 86%
“…At the end of this process, 27 studies were selected, each assessing patients with idiopathic autism (i.e., DSM-IV diagnoses of either Autistic Disorder, Asperger's Disorder or Pervasive Developmental Disorder Not Otherwise Specified, PDD-NOS), measuring head circumference in autistic patients and providing the percentage of macrocephalic individuals (Bolton et al, 1994;Bailey et al, 1995;Woodhouse et al, 1996;Davidovitch et al, 1996;Stevenson et al, 1997;Lainhart et al, 1997;Skjeldal et al, 1998;Fombonne et al, 1999;Ghaziuddin et al, 1999;Fidler et al, 2000;Miles et al, 2000;Gillberg and de Souza, 2002;Deutsch and Joseph, 2003;Torrey et al, 2004;Dementieva et al, 2005;Lainhart et al, 2006;Sacco et al, 2007;Van Daalen et al, 2007;Webb et al, 2007;Miles et al, 2008;Chawarska et al, 2011;Davidovitch et al, 2011;Ververi et al, 2012;Chaste et al, 2013;Froehlich et al, 2013;Grandgeorge et al, 2013;Cederlund et al, 2014). For each selected study, macrocephaly was defined as a head circumference above the 97 th percentile.…”
Section: 2study Selection Criteriamentioning
confidence: 99%
“…In some disorders there appears to be an overall shift in mean brain volume that goes beyond what might be expected from body-size considerations. For example, in autistic children, whole brains are, on average, larger than in matched, typically developing individuals [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28] (although microcephaly is also sometimes observed, if infrequently, in autistic children). 26 In contrast, it has been reported that children with attention-deficit/hyperactivity disorder have smaller whole brain volumes than normal, 29 though this finding is controversial.…”
Section: Allometrymentioning
confidence: 99%